2010
DOI: 10.1175/2009mwr2760.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of African Easterly Wave Structures and Their Role in Influencing Tropical Cyclogenesis

Abstract: Composite structures of African easterly waves (AEWs) that develop into named tropical cyclones in the Atlantic are compared and contrasted with nondeveloping AEWs using the 40-yr ECMWF Re-Analysis (ERA-40) data and satellite brightness temperature between 1979 and 2001. Developing AEWs are characterized by a more distinctive cold-core structure two days before reaching the West African coast. As they move westward, the convective activity increases further in the vicinity of the Guinea Highlands region. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 28 publications
23
98
0
Order By: Relevance
“…A composite study of AEWs by Hopsch et al (2010) found results consistent with the results of the present study. They composited wave structures for developing and nondeveloping waves for the time of passage of AEWs at 158W (the west coast of Africa) as well as 2 days before and after.…”
Section: E Other Composite Studiessupporting
confidence: 92%
“…A composite study of AEWs by Hopsch et al (2010) found results consistent with the results of the present study. They composited wave structures for developing and nondeveloping waves for the time of passage of AEWs at 158W (the west coast of Africa) as well as 2 days before and after.…”
Section: E Other Composite Studiessupporting
confidence: 92%
“…In addition, AEWs characterized by stronger low-level (850 mb) circulations and high relative humidity at the West African coast are more likely than weaker AEWs to undergo tropical cyclogenesis (7). However, strong winds associated with southern-and northern-track AEW vortices can advect dry Saharan air downstream of the AEW and impede development into a tropical cyclone entirely, or can delay tropical cyclogenesis until the wave reaches favorable environmental conditions farther west in the Atlantic basin (7,28). Further, although there is much evidence that northern-track waves can influence tropical cyclogenesis, in the present climate, many of the northern-track waves weaken as they reach the eastern Atlantic, or track north of the MDR (7,27).…”
Section: Resultsmentioning
confidence: 99%
“…However, compared with the southern vortices, the northern vortices are less efficient at undergoing tropical cyclogenesis. As the northern vortices propagate westward into the Atlantic, they often advect relatively dry Saharan air, known as the Saharan Air Layer, downstream of the wave trough (7). As a result of the dry air advection, northern-track vortices that do transition to tropical cyclones often do not undergo tropical cyclogenesis until they reach the Western Atlantic, where environmental conditions are more favorable for development (28).…”
Section: Greenhouse Gas Forcing | Cmip5mentioning
confidence: 99%
“…AEWs play a significant role in the modulation of rainfall (e.g. Fink and Reiner, 2003) over West Africa and also act as a precursor for tropical storms and hurricanes in the Atlantic (Landsea and Gray, 1992;Avila and Pasch, 1992;Thorncroft and Hodges, 2001;Zawislak and Zipser, 2010;Hopsch et al, 2010). Hence, the current lack of forecast ability has direct consequences on the forecasting of these events also.…”
Section: Introductionmentioning
confidence: 99%